Full-fault-tolerant single-phase 13-level cascaded multilevel inverter with modified H-bridge modules - Agarwal S.; Kapoor A.K. (My University, 2025)
This paper presents a 13-level fully fault-tolerant single phase cascaded multilevel inverter based on modified H-bridge modules. The inverter can operate normally with the failure of any one switch. The failure mode could either be short-circuit or open-circuit. To make the system fully fault-tolerant, an additional redundant module is used, thiscan be bypassed during normal operation. A modified level shifted PWM scheme is used to generate the gating signals of the switches so that during normal operation all the modules are equally used. A fault detection algorithm is presentedthat requires only the output voltage measurement. The fault detection works on the basis, that when a fault occurs, the output voltage deviates from the expected voltage. Post faultdetection, a fast and reliable method is proposed, that modifies the gating signals to continue with the normal operation of the inverter. Simulations are carried out to verify the proposed fault detection and correction algorithm. © 2018 IEEE.